2023
DOI: 10.3390/nano13142151
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mn1−xGexBi2Te4 Electronic Structure under Variation of Ge Content

Tatiana P. Estyunina,
Alexander M. Shikin,
Dmitry A. Estyunin
et al.

Abstract: One of the approaches to manipulate MnBi2Te4 properties is the magnetic dilution, which inevitably affects the interplay of magnetism and band topology in the system. In this work, we carried out angle-resolved photoemission spectroscopy (ARPES) measurements and density functional theory (DFT) calculations for analysing changes in the electronic structure of Mn1−xGexBi2Te4 that occur under parameter x variation. We consider two ways of Mn/Ge substitution: (i) bulk doping of the whole system; (ii) surface dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…While the formation of a plateau with a minimum energy gap in the extended concentration range of 30-50% is evident, the underlying physical processes responsible for these observed changes in the electronic structure remain to be investigated. One potential explanation, as suggested in previous studies 36,37,39 , is a possible transition to a WSM state within the region of the minimum energy gap. In this study, we aim to conduct a detailed analysis of the potential transition to such a state in Mn 1−x Ge x Bi 2 Te 4 and to identify the factors influencing the occurrence of various TPTs within this system, including the transition from the antiferromagnetic TI state to the WSM state.…”
Section: Investigation Of Possible Tpts and Formation Of Wsm State In...mentioning
confidence: 63%
See 3 more Smart Citations
“…While the formation of a plateau with a minimum energy gap in the extended concentration range of 30-50% is evident, the underlying physical processes responsible for these observed changes in the electronic structure remain to be investigated. One potential explanation, as suggested in previous studies 36,37,39 , is a possible transition to a WSM state within the region of the minimum energy gap. In this study, we aim to conduct a detailed analysis of the potential transition to such a state in Mn 1−x Ge x Bi 2 Te 4 and to identify the factors influencing the occurrence of various TPTs within this system, including the transition from the antiferromagnetic TI state to the WSM state.…”
Section: Investigation Of Possible Tpts and Formation Of Wsm State In...mentioning
confidence: 63%
“…As the Ge concentration approaches 90%, the states of the upper cone shift back towards lower binding energies, again forming a pronounced band gap. The ARPES data then resemble those more characteristic of Mn-doped GeBi 2 Te 4 , featuring the bulk band gap and TSS branches in the region of their intersection with the edge of the VB (for comparison, see 37,38 for GeBi 2 Te 4 ).…”
Section: (B)mentioning
confidence: 73%
See 2 more Smart Citations
“…There are ternary TI compounds, such as A IV Bi 2 Te 4 , with the same R3m symmetry group as MnBi 2 Te 4 [13,27], allowing for arbitrary ratios of Mn substitution in solid solutions (Mn 1−x A IV x )Bi 2 Te 4 . Several studies [28][29][30][31][32] have demonstrated the synthesis of these crystals and confirmed the absence of additional substitution defects, as in the case of substitution of Sb for Bi atoms. Moreover, this substitution appears to be isovalent and does not introduce any additional charge according to ARPES studies [32].…”
mentioning
confidence: 66%